2015
DOI: 10.1515/cclm-2014-1084
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of BNP in children undergoing surgery for congenital heart disease: analysis of prediction models incorporating standard risk factors

Abstract: Our data indicates that BNP may improve the risk prediction in pediatric cardiac surgery, supporting its routine use in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 21 publications
0
27
0
1
Order By: Relevance
“…Various studies have shown that post-operative BNP, lack of decrease in BNP post-operatively were all strongly related to poor hemodynamics or adverse outcomes after a cardiac surgery[18,19]. Bobik et al[20] evaluated the value of NT-pro BNP in patients with atrioventricular septal defects (AVSD) preoperatively.…”
Section: B-type Natriuretic Peptide and N-terminal Segment Of Pro-b-tmentioning
confidence: 99%
“…Various studies have shown that post-operative BNP, lack of decrease in BNP post-operatively were all strongly related to poor hemodynamics or adverse outcomes after a cardiac surgery[18,19]. Bobik et al[20] evaluated the value of NT-pro BNP in patients with atrioventricular septal defects (AVSD) preoperatively.…”
Section: B-type Natriuretic Peptide and N-terminal Segment Of Pro-b-tmentioning
confidence: 99%
“…There are sufficient evidences on the prognostic role of BNP-NT-proBNP in children undergoing cardiac surgery. [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] As reported by multiple authors. BNP levels (especially those measured preoperatively) were independently associated with important parameters of outcome, including the duration of mechanical ventilation, intensive care unit stay, need for inotropic support, and low cardiac output syndrome.…”
Section: Bnp In Children Undergoing Cardiac Surgery For Correction/pamentioning
confidence: 80%
“…This opposite pattern of BNP kinetics after surgery is probably the result of multiple factors including: the higher severity of CHD with neonatal presentation, the complexity of neonatal surgical procedures. 90 In addition, the maturational variations in BNP response during the first weeks of life need also to be taken into account. 69,70 Usually biomarker values tend to progressively decrease after the initial peak reached within the first 24 hours postsurgery.…”
Section: Bnp In Children Undergoing Cardiac Surgery For Correction/pamentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors (16,17) use biomarkers as brain natriuretic peptide or Troponin I that may improve the risk prediction in pediatric cardiac surgery, supporting its routine use in this setting.…”
mentioning
confidence: 99%